Infective endocarditis: diagnostic difficulties - N. S. Chipigina (Klinicist, 2020)
In recent decades, against the background of incidence rate increasing, infectious endocarditis (IE) remains in the category of diseases with a high mortality and a “difficult diagnosis”. According to different studies, 5.2–14.8 % of IE cases were detected only at autopsy or heart surgery, and 27–42.8 % of IE cases with fatal outcome were not diagnosed before death. In 25–66 % patients infectious endocarditis was diagnosed later than 1 month from the onset of symptoms (including later than 3 months in almost a quarter of patients). Late diagnosis, considered as one of the independent risk factors for an unfavorable prognosis of IE (relative risk 2.1), is most frequent with IE in elderly patients. The generally accepted diagnostic criteria of IE, providing a standardized approach to the diagnosis of IE, rely on laboratory and instrumental evidence of bacteremia and visualization of vegetations and signs of valve destruction, as major clinical diagnostic criteria. However, a diagnosis of IE is not suspected at an outpatient stage in 54–79 % of patients, so the necessary transthoracic echocardiographic examination and bacteriological blood tests are not performed. In 84 % cases of right heart valves IE and 27 % of left heart valves IE extracardiac manifestations of the disease due to cardiogenic emboli, immunocomplex mechanisms, or systemic inflammation were initially regarded as an independent disease and patients were hospitalized with incorrect diagnosis. Most often, such masks are associated with involvement of lungs, nervous system, and kidneys, less often rheumatological, vascular, hematological guise and the onset with myocardial infarction or acute abdominal pain are noted. The lecture analyzes the causes of IE diagnosis errors and describes clinical situations that allow suspecting IE, as well as situations in which IE must be considered with a differential diagnosis. Authors emphasize that timely clinical suspicion, with availability of modern effective heart imaging and bacteriological studies remains essential basis for early IE diagnosis.